4 - A Review of Youth Violence Theories: Developing Interventions to Promote Sustainable Peace in Ilorin, Nigeria - Ali Arazeem Abdullahi,; Mariam Seedat-Khan,; Saheed Olanrewaju Abdulrahman, (African Sociological Review, 2016)
Ilorin is located in North Central Nigeria with an estimated population above two million people. For some time now, Ilorin has been regarded as the most “peaceful” State Capital in the North Central geo-political zone; due to rare outburst of violence and criminality. However, in the recent past, the peaceful atmosphere of the State Capital has been under serious threat owing to frequent outburst of youth violence, particularly in socially disadvantaged neighbourhoods (SDNs). Consequently, youth violence has attracted the attention of policy makers and stakeholders in the State Capital, thereby occupying an important space in local discourses. In this paper, we undertake a review of theories of violence to understand the etiology of youth violence in Ilorin in particular and Nigeria as a whole, and assess the implications of these theories for developing strategies and policy frameworks for promoting long-lasting, sustainable peace.